JURIDICAL ANALYSIS OF THE POSITION OF NOTARY REGARDING CONCURRENT POSITIONS AS LECTURER IN HIGHER EDUCATION - Sulthan Hafizh; Fitria Dewi Navisa; Sunardi Sunardi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
University or College is a place for people or communities who want to study at a higher level. In this University there are several teaching programs, namely Diploma, Bachelor, Master, Doctoral, Professional and Specialist Programs. In organizing education carried out by this University, it is divided into several faculties that carry out scientific and professional education in specific disciplines. Lecturers are educational staff who have special experience in a field of profession that they are pursuing, in teaching in the Postgraduate Notary Program, teachers or lecturers are needed who also hold positions as notaries. However, in practice, this has caused problems because in National law that concerning Notary Positions, a notary is prohibited from holding a position in a business entity, either state-owned or privately owned. This raises a conflict, on the one hand, this Notary is not allowed to hold a position in a business entity, but in terms of the world of education, especially in universities that have a law faculty and a postgraduate program majoring in law, lecturers or teachers who have expertise in the field of notaries are very much needed. However, based on several exceptions and positive laws that indirectly regulate this matter, Government Regulation Number 60 of 1999 concerning Higher Education regulates extraordinary Lecturers, Law Number 14 of 2005 concerning Teachers and Lecturers, in the eyes of the law, notaries who become lecturers can hold the status of general notary officials and lecturers.